Role of poly (ADP-ribose) polymerase-1 and cytokines in acute renal injury in elderly Chinese patients with diabetes mellitus - Cao L (Dove Medical Press, 2017)
Li Cao, Yan Liu, Li Zhang, Yanfei Wei Intensive Medicine, Nanxishan Hospital of Guangxi Zhuang Autonomous Region, Guilin, Guangxi, China Objective: The primary objective of this study was to evaluate whether the polymorphism of poly (ADP-ribose) polymerase-1 (PARP-1) is involved as a potential risk factor in the development of acute renal injury in elderly Chinese patients with diabetes mellitus. Subjects and methods: In this pilot study, diabetic patients of either gender (aged ≥65 years) with a confirmed diagnosis of acute renal injury and individuals with no clinical symptoms of acute renal injury were enrolled at Nanxishan Hospital of Guangxi Zhuang Autonomous Region, China. Genetic polymorphism of PARP-1 was assessed using polymerase chain reaction-restriction fragment length polymorphism assay. Cytokine levels (interleukin [IL]-6, IL-1β and tumor necrosis factor-alpha) were measured in the serum samples by sandwich enzyme-linked immunosorbent assay technique. Results: A total of 130 Chinese patients with acute renal injury and 130 Chinese individuals with no clinical symptoms of acute renal injury were included. We found that the patients with GG genotype and carriers of the G and C alleles of PARP-1 were at high risk of developing acute renal injury. Moreover, del/ins polymorphism of the NF-κB1 gene was also found to be associated with acute renal injury. In addition, the levels of IL-6, IL-1β and tumor necrosis factor-alpha were significantly increased in patients with acute renal injury (p<0.05). Conclusion: Our findings showed the involvement of PARP-1 polymorphisms in the development of acute renal injury in Chinese individuals. This study identified the involvement of two SNPs of PARP-1 (C410T and G1672A) in development of acute renal injury among Chinese diabetic patients. Also, increased expression of C and G alleles of PARP-1 can be considered as one of the potential risk factors for developing acute renal injury. Increased serum cytokine levels can be considered as one of the potential risk factors for developing acute renal injury. Keywords: acute renal injury, poly (ADP-ribose) polymerase-1, diabetes mellitus, polymorphism